A Service-Dominant Logic Perspective on Technology-Enabled Relationship Marketing and Value Co-Creation in B2B Facility Management Digital Platforms - Ni Made Ariasih; Bambang Satya Wienantono (Research Synergy Foundation, 2026)
This study repositions Relationship Marketing (RM) from a customer-management tool to a risk-governance mechanism for high-risk Facility Management (FM) services at Telkom Property’s Bali branch. Using the Service-Dominant Logic framework, it examines how My Birawa, a digital service platform, supports operational trust and value-in-use. This support comes from integrating technical reliability with relational governance. The study uses a qualitative approach and a multiple case study design. It examines two Telkom Property companies managing cleaning and security services in commercial buildings. Data were collected through semi-structured interviews, field observations, and document analysis. Thematic analysis was used to interpret the data. The research has three key findings. First, My Birawa acts as a digital infrastructure that improves operational efficiency by accelerating problem resolution (Mean Time to Resolution) and strengthening accountability through KPI-based monitoring. Specifically, the platform has an average effectiveness rating of 4.67 out of 5, with a 100% user adoption rate. Second, the platform enables value co-creation through cross-functional integration and codifies location-specific knowledge. As a result, this strengthens relationship equity and creates non-financial switching barriers for clients. Third, its effectiveness is influenced by technical interdependencies, such as Wi-Fi stability, as well as by fragmented tenant coordination.